29.5k views
4 votes
Rearrange the equation so uuu is the independent variable.
-12u+13=8w-3

User VGaur
by
5.4k points

2 Answers

5 votes

Answer:

u = 8w-16 /-12 or = - 8w-16/12 both mean the same due to the a/-b- = -a/b rule. Then you can factor out the rest. note the fnew subtraction changes mean the same as - (a/b) and should show without brackets as a centre pointing whole fraction subtraction sign.

Explanation:

-12u -13 = 8w-3

-12u+13 -13 = 8w-3-13 Eliminate -13 by +13 both sides

-12u = 8w-16 So you are left with one value left side.

-12u/-12 = 8/-12 - 16/-12 Then divide all values by -12 to find value for u and keep the subtraction as 8 never had subtraction sign and no multiplication .

u = 8w-16 /-12 Then you can factor out the rest

This has made u the independent variable then you have a choice to continue showing or ignore u; as u =

= - 8(w-2)/12 Step 1 Factor with subtraction change from -12 to - central fraction

= - 2(w-2)/3 Step 2 Simplify with new minus sign for central fraction to replace a/-b

User Gustavomcls
by
5.1k points
3 votes

Answer:

The answer is W = -3/2u + 2

Explanation:

Look at attachment:

Hope this helps! :)

Rearrange the equation so uuu is the independent variable. -12u+13=8w-3-example-1
User Conor Svensson
by
5.5k points